Distance education in the conditions of 2020 - risks and signs - Nataliya Volotovska (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
This article deals with the benefits and risks of distance learning programs being based on the modern information sources. Alco the personal experience of distance teaching, released by teaching stuff of the Department of Physiology, Bioethics and Biosafety, as well as research of psychological comfort during working hours. Personal ways to solve difficulties were in that period are presented, opportunities of effective implementation of obtained experience are proposed, including the back to classical studying scenario.